Ludwig von Mises and the "Ordo-interventionists": More than just aggression and contempt? - Stefan Kolev (Duke University, Center for the History of Political Economy (CHOPE), 2016)
This paper explores the four decades of intellectual relationship between the Austrian School economist Ludwig von Mises (1881-1973) and two major representatives of German ordoliberalism, Walter Eucken (1891-1950) and Wilhelm Röpke (1899-1966). The timespan covered starts in the early 1920s and terminates with Röpke's passing in 1966, a period featuring numerous encounters in person and several debates in published works, accompanied by exchange in correspondence. The central goal of the paper is to provide a more nuanced understanding of the reasons for the hostile climate and the confrontation patterns than earlier narratives in secondary literature. A key tool is the technique of embedding the scholarly component of the interactions into a complex network of interpersonal relationships. The four decades are separated into five distinct phases with differently nuanced communication patterns: 1) early socialization echoing the animosities between the Austrian School and the Historical School; 2) initial debates in the 1920s and early 1930s on business cycle theory and policy where seniority and maturity play an important role; 3) clashes on political economy and social philosophy at the Colloque Walter Lippmann in 1938 and during the two initial decades of the Mont Pèlerin Society after 1947; 4) coexistence during the German "economic miracle"; 5) exchanges in the 1960s, including a discussion of archival materials never published before about Mises' only honorary doctorate in economics, awarded to him by the University of Freiburg in 1964. Based on this historical account at the heart of the paper, conjectures are formulated as to why - despite the common ground in the inquiries pursued - the protagonists continuously fail to engage in more fruitful scholarly debates, and hypotheses are formulated about the substantive core at stake. In addition, a critical overview of selected strands within the extensive historiographic literature exploring the Austrian School and ordoliberalism in recent decades is provided, including a specific reading of the concept of neoliberalism.
Keywords: A11; B25; B31; H10; N44; P16; 330; Ludwig von Mises; Walter Eucken; Wilhelm Röpke; Austrian School; Mont Pèlerin Society; ordoliberalism; neoliberalism